2014
DOI: 10.1007/s11274-014-1654-8
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Lactobacillus plantarum from traditional Italian wines

Abstract: In this study, 23 samples of traditional wines produced in Southern Italy were subjected to microbiological analyses with the aim to identify and biotype the predominant species of lactic acid bacilli. For this purpose, a multiple approach, consisting in the application of both phenotypic (API 50CHL test) and biomolecular methods (polymerase chain reaction-denaturing gradient gel electrophoresis and 16S rRNA gene sequencing) was used. The results showed that Lactobacillus plantarum was the predominant species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Biogeography studies, which show that microbial communities associated with a wine region depend on the environment and the vine variety, corroborate this idea [11]. Moreover, although uncommon, some research has shown the prevalence of malolactic species different from O. oeni in certain wine regions, as well as a growing interest in these to be used as starters given their favorable characteristics [12][13][14]. A recent starter formulation made by Lallemand Inc., based on a selected L. plantarum strain, confirms this evidence.…”
Section: Introductionmentioning
confidence: 90%
“…Biogeography studies, which show that microbial communities associated with a wine region depend on the environment and the vine variety, corroborate this idea [11]. Moreover, although uncommon, some research has shown the prevalence of malolactic species different from O. oeni in certain wine regions, as well as a growing interest in these to be used as starters given their favorable characteristics [12][13][14]. A recent starter formulation made by Lallemand Inc., based on a selected L. plantarum strain, confirms this evidence.…”
Section: Introductionmentioning
confidence: 90%
“…Testa et al (2014) have undertaken a similar study examining the biodiversity of L. plantarum strains from traditional Italian wines. Testa et al (2014) have undertaken a similar study examining the biodiversity of L. plantarum strains from traditional Italian wines.…”
Section: Bartowsky Et Al Emerging Trends In Mlf 665mentioning
confidence: 99%
“…As mentioned previously in this review, however, Testa et al (2014) screened L. plantarum strains sourced from different artisanal wineries located in various areas of Southern Italy to select potential L. plantarum strains as candidate starter cultures with the aim of enhancing regional character. As mentioned previously in this review, however, Testa et al (2014) screened L. plantarum strains sourced from different artisanal wineries located in various areas of Southern Italy to select potential L. plantarum strains as candidate starter cultures with the aim of enhancing regional character.…”
Section: Enhancing Regionality Of Wine Through Mlfmentioning
confidence: 99%
See 2 more Smart Citations